Plz answer this question
No spam answers plz
Attachments:
![](https://hi-static.z-dn.net/files/dce/68bc800bbf91eec25138255bf52928da.jpg)
Answers
Answered by
1
Answer:hope it helps u
Step-by-step explanation:
(i) xSinx
We apply d(uv)/dx here
d(uv)/dx=u (dv/dx)+v(du/dx)
Here u=x and v=Since
Therefore,
d{xSinx}/dx=x{d(Sinx/dx)}+Sinx{dx/dx}
=xCosx+Sinx(1)
=xCosx+Sinx
This is the answer...
(ii)x^4+Cosx
=d{x^4}/dx+d{Cosx}/dx
=4x^3-Sinx
Since d{x^n}/dx=n{x^(n-1)} & d{Cosx}/dx= -Sinx
(iii) x/Sinx
It is in the form of (u/v)
We know, d(u/v)=[v{du/dx}-u{dv/dx}] / v^2
Therefore,
d{x/Sinx}/dx=[Sinx{dx/dx}-x{d(Sinx)/dx}]/ Sin^2(x)
=[Sinx(1)-x(Cosx)]/Sin^2(x)
=(Sinx-xCosx)/Sin^2x
={Sinx/Sin^2x}-{xCosx/Sin^2x}
={1/Sinx}-{xCosx/Sin^2x}
This is the answer.
Note that the third answer given in your notebook is wrong.There should be minus sign instead of plus sign in final answer.
Similar questions